2017
DOI: 10.1177/0306624x17740016
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis and Sexual Offending: A Review of Current Literature

Abstract: Sexual offending is a public health concern and societal risk requiring a multi-disciplinary approach. While current data give an indication of the frequency of sexual victimization, these figures likely underestimate the severity of the concern as many of these incidents go unreported. And while sex offender research has increased over the past several decades, particular attention to those offenders with severe mental illness remains limited. In this descriptive review, literature describing sex offenders wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
(56 reference statements)
0
14
0
Order By: Relevance
“…Nationally in the United States, 2.3% of people on sex offender registries are female (Ackerman, Harris, Levenson, & Zgoba, 2011). A growing body of literature is examining females with sexual offenses (Lewis & Dwyer, 2018; Morgan & Long, 2018; Williams, Gillespie, Elliott, & Eldridge, 2017), and with time, we may have a better understanding of female veterans who commit sexual offenses. We did not examine active duty military members nor are we able to determine if a veteran’s sexual offense was committed after military service or during military service.…”
Section: Discussionmentioning
confidence: 99%
“…Nationally in the United States, 2.3% of people on sex offender registries are female (Ackerman, Harris, Levenson, & Zgoba, 2011). A growing body of literature is examining females with sexual offenses (Lewis & Dwyer, 2018; Morgan & Long, 2018; Williams, Gillespie, Elliott, & Eldridge, 2017), and with time, we may have a better understanding of female veterans who commit sexual offenses. We did not examine active duty military members nor are we able to determine if a veteran’s sexual offense was committed after military service or during military service.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore likely that the psychiatrists in question chose a less specific diagnosis within the psychotic disorder spectrum. Despite considerable variations (7), a recent review found that 5–10% of the subjects in sex offender samples are diagnosed with psychotic disorders (13), with similar prevalence rates in a Swedish context (8). Logically, forensic treatment samples demonstrate higher prevalence rates (7,13).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, MDSOs who present symptoms from the psychotic disorder spectrum represent a subgroup of sex offenders that offers unique challenges with regard to motivations, risks, and treatment needs. In a 2018 review on sex offenders with psychotic disorders, Lewis & Dwyer addressed several areas requiring more research (13). This included further studies on female offenders, offenders found not guilty by reason of insanity, and possible effects of comorbidity.…”
mentioning
confidence: 99%
“…Rehabilitation is based on the underlying principle that people can and want to change and is delivered though a Cognitive-Behavioural framework that uses strength-based models and pro-social behaviour modelling [1, 12••, 62, 63••, 64-68]. In recent years, we have seen a de-pathologising of people who commit sexual offences as it is no longer accepted that all people who commit sexual offences have a severe mental illness [69][70][71]. Instead, we are seeing that inclusion IN treatment programmes is being determined not by their offence but instead by level of anti-sociality, any co-morbidities and risk of re-offending [69][70][71].…”
Section: Current Approaches To Community Risk Managementmentioning
confidence: 99%